BIMBINGAN DAN PELATIHAN SOFT SKILL BAGI ANAK BERKEBUTUHAN KHUSUS DI YAYASAN PEMBINAAN ANAK CACAT (YPAC) MALANG - Lilies Nur Ainie; Nilawati Fiernaningsih; Siti Nurbaya; Mustofa Hadi; Halid Hasan (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2019)
The purpose of this activity is to provide guidance and training on developing soft skills for children with special needs, improving soft skills, and how to find their potential in children with special needs, helping provide an understanding that the development of soft skills.This activity is a community service activity (PKM) with the form of activities carried out with the following material: Educational Materials, Contest, and Discussion of Problems.The results of this activity are to improve the discourse of the participants of the Malang Disability Child Development Foundation (YPAC), Improve the members knowledge of selected basic skills with some special considerations, namely discovering the potential of the soft skills mastered, and Improving the relationship between Malang State Polytechnic and the community , especially in the Malang Disability Development Foundation (YPAC).